2018
DOI: 10.1107/s1600577517018148
|View full text |Cite
|
Sign up to set email alerts
|

Real-space analysis of radiation-induced specific changes with independent component analysis

Abstract: A method of analysis is presented that allows for the separation of specific radiation-induced changes into distinct components in real space. The method relies on independent component analysis (ICA) and can be effectively applied to electron density maps and other types of maps, provided that they can be represented as sets of numbers on a grid. Here, for glucose isomerase crystals, ICA was used in a proof-of-concept analysis to separate temperature-dependent and temperature-independent components of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Glucose isomerase (GI), also called xylose isomerase, from Streptomyces rubiginosus was purchased from Hampton Research (23). Protein slurry was dialyzed three times against excess of dH 2 O and concentrated to ∼40 mg/ml with Amicon filter.…”
Section: Methodsmentioning
confidence: 99%
“…Glucose isomerase (GI), also called xylose isomerase, from Streptomyces rubiginosus was purchased from Hampton Research (23). Protein slurry was dialyzed three times against excess of dH 2 O and concentrated to ∼40 mg/ml with Amicon filter.…”
Section: Methodsmentioning
confidence: 99%
“…Glucose isomerase (GI), also called xylose isomerase, from Streptomyces rubiginosus was purchased from Hampton Research. Protein slurry was dialyzed three times against an excess of distilled H 2 O and concentrated to $40 mg ml À1 with an Amicon filter (Borek et al, 2018).…”
Section: Protein Expression Purification and Grid Preparationmentioning
confidence: 99%
“…These phenomena are then followed by various chemical changes involving, for instance, the elongation and eventual breaking of disulphide bonds, the decarboxylation of glutamate and aspartate residues and the breaking of covalent bonds between the protein backbone and the metal centres. Gerstel et al [1] provide an exhaustive methodological discussion concerning different susceptibilities empirically observed for all the different types of specific damage described in the literature, while Borek and collaborators recently provided a promising method to discern temperature-dependent changes from other types of change [5]. On the other hand, combined measurements based on single-crystal X-ray diffraction, small angle scattering and radiolysis experiments have shown that hydrogen gas formed in the sample during irradiation, rather than bond cleavage, is mainly responsible for the loss of high-resolution information [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we will outline how specific damage events in crystallographic models can be interpreted in terms of local structural deformations caused by the population and depopulation of virtual and occupied electronic states in the close vicinity of the Fermi energy of the perfect crystal. Previous reports in the literature have addressed and quantified the local changes, but unfortunately, due to the lack of a unifying model, a quantification of this effect has proved to be very subjective and system dependent (although procedures for radiation damage corrections have been refined empirically to a point where a systematic and automated assessment is possible [1,5,15]). It is our view that single crystal macromolecular crystallography oscillation datasets are unsuitable for assessing the structural changes caused by specific damage, since they rely on information obtained too long (seconds) after the initial interaction of the X-ray beam with the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation